Frailty transitions and prevalence in an ageing population: longitudinal analysis of primary care data from an open cohort of adults aged 50 and over in England, 2006–2017 - Walsh, B; Fogg, C; Harris, S; Roderick, P; de Lusignan, S; England, T; Clegg, A; Brailsford, S; Fraser, SDS (Oxford University Press, 2023)
Introduction: frailty is common in older adults and is associated with increased health and social care use. Longitudinal information is needed on population-level incidence, prevalence and frailty progression to plan services to meet future population needs.